The neural basis of non-verbal communication—enhanced processing of perceived give-me gestures in 9-month-old girls - Bakker, Marta; Kaduk, Katharina; Elsner, Claudia; Juvrud, Joshua; Gustaf Gredebäck, (Frontiers in Psychology, 2015)
This study investigated the neural basis of non-verbal communication. Event-related potentials were recorded while 29 nine-month-old infants were presented with a give-me gesture (experimental condition) and the same hand shape but rotated 90 degrees, resulting in a non-communicative hand configuration (control condition). We found different responses in amplitude between the two conditions, captured in the P400 ERP component. Moreover, the size of this effect was modulated by participants’ sex, with girls generally demonstrating a larger relative difference between the two conditions than boys.